Pemberdayaan Tim Pengembang Kurikulum (TPK) Pendidikan Dasar dan Menengah - Ambari Sutardi (Jurnal Pendidikan dan Kebudayaan, 2011)
The objective of the study is to get information from some sample areas about: the establishment of curriculum developers team (CDT) for basic and secondary education; the structure of its caretaker, who and how many of its members; the availability of a budget needed; the members‘ understanding of the government policies related to curriculum; the empowerment of its members to do their main tasks among other things: socializing the policies and helping schools within basic and secondary educations writing up their respective curriculum; and school-based curriculum (S-BC) implementation. The data shows that all sample districts/municipalities have already established CDT; there is its caretaker structure with a various number of members; there is no sufficient budget in some districts/municipalities; there are some degrees of the members’understanding about the government policies related to curriculum; Districts/Municipalities Ministry of National Education empowered only some of the members socializing the government policies and helping schools writing up their curriculum as their main tasks; the implementation of S-BC was still uneven. ABSTRAK Tujuan studi dimaksudkan untuk memperoleh informasi dari daerah sampel tentang: Pembentukan Tim Pengembang Kurikulum (TPK) pendidikan dasar dan menengah; struktur kepengurusan, siapa dan berapa jumlah anggotanya; keberadaan dana bagi TPK; pemahaman anggota terhadap kebijakan Pemerintah yang berkaitan dengan kurikulum; pemberdayaan mereka melaksanakan tugas pokok antara lain mensosialisasikan kebijakan dan mendampingi sekolah menyusun kurikulum; dan pelaksanaan kurikulum di sekolah. Hasil studi menunjukkan bahwa semua daerah sampel telah membentuk TPK; ada struktur kepengurusannya dengan jumlah anggota bervariasi; dana belum tersedia secara memadai di beberapa daerah; tingkat pemahaman responden terhadap kebijakan bervariasi; hanya sebagian anggota TPK yang diberdayakan sesuai TUPOKSInya; pelaksanaan KTSP di sekolah belum merata.